Effects of alterations of primer-binding site sequences on human immunodeficiency virus type 1 replication. - Li, X (1994)
The human immunodeficiency virus type 1 genomic RNA primer-binding site (PBS) sequence comprises 18 nucleotides which are complementary to those at the 3' end of the replication initiation primer tRNA(3Lys). To investigate the role of the PBS in viral replication, we either deleted the original wild-type PBS (complementary to tRNA(3Lys) or replaced it with DNA sequences complementary to either tRNA(1,2Lys) or tRNA(Phe). Transfection of COS cells with such molecular constructs yielded similar levels of viral progeny that were indistinguishable with regard to viral proteins and tRNA content. Virus particles derived from PBS-deleted molecular clones were noninfectious for MT-4, Jurkat, and CEM-T4 cells. However, infectious viruses were derived from constructs in which the PBS had been altered to sequences complementary to either tRNA(1,2Lys) or tRNA(Phe), although mutated forms showed significant lags in replication efficiency in comparison with wild types. Molecular analysis of reverse-transcribed DNA in cells infected by the mutated viruses indicated that both tRNA(1,2Lys) and tRNA(Phe) could function as primers for reverse transcription during the early stages of infection. Sequencing of full-length proviral DNA, obtained 6 days after infection, revealed the mutated PBS, indicating that a complete cycle of reverse transcription had occurred. During subsequent rounds of infection, reversion of the mutated PBS to wild-type sequences was observed, accompanied by increased production of viral gene products. Reversion to wild-type PBS sequences was confirmed both by specific PCR analysis, using distinct primer pairs, and by direct sequencing of amplified segments. We also performed endogenous in vitro reverse transcription experiments in which synthesis of minus-strand strong-stop viral DNA was primed from a synthetic RNA template containing a PBS complementary to various tRNA isoacceptors. These results showed that tRNA(3Lys) was a much more efficient primer of such reactions than either tRNA(1,2Lys) or tRNA(Phe).